SISTEM INFORMASI PENGGAJIAN DAN TUNJANGAN KINERJA DAERAH BERBASIS WEBSITE PADA KANTOR WALIKOTA GORONTALO - Syaifuddin S (Universitas PGRI Semarang, 2018)
Every Employee who works at an agency is entitled to a salary based on the rules and conditions of the applicable payroll. The issue of the granting of salary is not only important because it is the main thrust of a person to be a clerk, but also because it had rendered paycheck a major role against the morale of the employees, so that required a system processing the right payroll data. At the initial interview was found to the problem of the difficulty of doing the calculation of salaries of employees include base salary and allowances as well as the creation of regional performance reports payroll employees each month. The staffing portion has actually been using computerized through an office application excel and acces to ease job but still prefers a constraint with the redundancies of data in the financial statements and the difficulty of making the staffing section had to add extra hours of work every month end. The methods used in this research is descriptive method. The results of this research are systems process payroll and payroll execution allows TKD and staffing allowances Division by a part as well as accelerate the process of reporting on management.